Bionomi nematoda puru akar (Meloidogynegraminicola) ) pada tanaman pa-di= Bionomy of Root-knot Nematode (Meloidogyne graminicola) on Rice - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT The research of Bionomy of Root-Knot Nematode (Meloidogyne graminicola) on Rice was done with the following objectives i.e.: 1) study on the biology of root-knot nematode on rice, and 2) study on the damaged of rice caused by M. graminicola. Biological study of M. graminicola was done in plastic pots. The observations were conducted on rice roots fixed with acid fuchsin lactophenol. Study on the effect of M. graminicola on the damage of rice was done in plastic pots. The pots were arranged in split split plot experiment with three replications. The observations were conducted at 35, 70 days after inoculation, and harvest. Three factors of experiment were used i.e.: irrigation methods, initial population levels of M. graminicola, and rice varieties. The research was done in the Plastic House and Nematology Laboratory, Faculty of Agriculture, Gadjah Mada University. The results of research are as follows: 1.The life cycle of M. graminicola is 20-21 days. Number of eggs per egg mass are 147-300 eggs. The percentage hatch of eggs are 63.0987.07 To. 2.Each treatment was affected by irrigation methods, initial population levels of M. graminicola, rice varieties, and there were significantly different between the treatments on the root damage level, plant growth, yield, and population of M. graminicola. 3. Plant growth on flooded rice during the growth stages of the crop, better than other irrigation methods.